Advancements in stress-testing methodologies for financial stability applications - Katarzyna Budnik; Aurea Ponte Marques; Saifeddine Ben Hadj; Oana-Maria Georgescu; Carla Giglio; Alberto Grassi; Agha Durrani; Juan Manuel Figueres; Paul Konietschke; Catherine Le Grand; Julian Metzler; Aljosa Ortl; et al. (European Central Bank (ECB), 2024)
This paper provides an overview of stress-testing methodologies in Europe, with a focus on the advancements made by the European Central Bank's Financial Stability Committee Working Group on Stress Testing (WGST). Over a four-year period, the WGST played a pivotal role in refining stress-testing practices, promoting collaboration among central banks and supervisory authorities and addressing challenges in the evolving financial landscape. The paper discusses the development and application of various stress-testing models, including top-down models, macro-micro models and system-wide models. It highlights the integration of new datasets and model validation efforts as well as the expanded use of stress-testing methodologies in risk and policy evaluation and in communication. The collaborative efforts of the WGST have demystified stress-testing methodologies and fostered trust among stakeholders. The paper concludes by outlining the future agenda for continued improvements in stress-testing practices.
Keywords: G21; G28; C58; G01; G18; 330; stress testing; prudential policies; uncertainty; macro-financial scenarios; Basel III; COVID19 mitigation; impact assessment; lending; economic activity; communication; Working Group on Stress Testing; financial system model